Application of Statistical Methods to the Assessment of Prices of Klaipeda City Apartments - Navickaitė, Roberta (Lithuanian Journal of Statistics, 2014)
The paper analyses the use of a nonlinear regression model, generalised linear model and generalised additive model(semi-parametric regression model) for creating real estate valuation models. These models are applied to data on transactions inKlaipeda city apartments. The aim is to create real estate valuation regression models applying various statistical methods and tocompare them with each other. The practical aspects of creating regression models are analysed and conclusions are presented in thepaper.